2014
DOI: 10.1007/s11096-014-9963-4
|View full text |Cite
|
Sign up to set email alerts
|

Medication regimen complexity in institutionalized elderly people in an aging society

Abstract: Background Complex medication regimens may adversely affect compliance and treatment outcomes. Complexity can be assessed with the medication regimen complexity index (MRCI), which has proved to be a valid, reliable tool, with potential uses in both practice and research. Objective To use the MRCI to assess medication regimen complexity in institutionalized elderly people. Setting Five nursing homes in mainland Portugal. Methods A descriptive, cross-sectional study of institutionalized elderly people (n = 415)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
53
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 27 publications
10
53
2
2
Order By: Relevance
“…[11][12][13][14][15] The median number of drugs that each patient received on hospital discharge in the pediatric group was two while that in the geriatric group was five (p<0.001). The median MRCI score was significantly higher in the geriatric age group (15.5) in comparison to the pediatric group (7.5) (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] The median number of drugs that each patient received on hospital discharge in the pediatric group was two while that in the geriatric group was five (p<0.001). The median MRCI score was significantly higher in the geriatric age group (15.5) in comparison to the pediatric group (7.5) (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] However, the studies differ with regard to the contribution of section A and C towards the final score. [15][16][17] We also assessed if gender was a factor that affected the number of drugs a patient received and if the MRCI score varied across genders. In the pediatric age group, the number of drugs prescribed and the MRCI score did not differ significantly between the genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This medication review should be particularly focused on benzodiazepines, other psychotropic medications, and medicines that contribute to a high drug burden index (ie, those with anticholinergic or sedative properties). 6,[32][33][34] Other interventions to prevent falls have been multifactorial in nature and have addressed risk factors pertaining to the individual (eg, strength and balance training) as well as his or her ability to safely interact with the environment. A meta-analysis by Cameron et al 35 reported that multifactorial interventions reduce falls and risk of falling in hospitals and may do so in nursing care facilities.…”
Section: Nonpharmacologicalmentioning
confidence: 99%
“…6,7 Osteoporosis treatment is a particularly challenging area in RACFs. The majority of residents in this setting are at high risk of suffering a fracture, 8 but only a minority receives treatment according to their level of risk.…”
mentioning
confidence: 99%